Trends in the prevalence of smoking in Russia during the transition to a market economy - Perlman, Francesca (BMJ Group, 2007)
BACKGROUND: Changes in smoking, particularly an increase in women, were predicted to follow the aggressive campaigns of multinational tobacco companies in transitional Russia. However, such changes have not yet been demonstrated unequivocally. OBJECTIVE: To examine smoking trends by gender, education and area of residence. METHODS: Data from 10 rounds of the Russia Longitudinal Monitoring Survey (1992–2003), consisting of more than 3000 men and 4000 women in each round, were used. The mean reported ages of first smoking in current smokers were compared between 10‐year birth cohorts. RESULTS: Between 1992 and 2003, smoking prevalence doubled among women from 6.9% (95% CI 6.3% to 7.6%) to 14.8% (13.9% to 15.7%) and increased among men from 57.4% (95% CI 56.0% to 58.8%) to 62.6% (61.1% to 64.1%). In both sexes, the rise was significantly greater in the least educated, markedly so in women (a doubling vs a 1.5‐fold rise in the most educated). Although prevalence of smoking among women was considerably higher in Moscow and St Petersburg than in rural areas, the dramatic threefold increase in prevalence in rural women was significantly greater than in the main cities (36%, p<0.001). The mean age of first smoking was significantly lower in women born after 1960, but in men it was stable between cohorts. CONCLUSIONS: For the first time, it has been shown unequivocally that smoking among women increased markedly during the transition to a market economy in Russia. The already high prevalence of smoking among men has continued to rise. These changes are likely to reflect the activity of the tobacco industry and provide further evidence of the harms of privatisation. Effective tobacco control policies are urgently needed.